ZnO nano/microstructures grown by laser assisted flow deposition - Rodrigues, J.
Nano/microstructures of zinc oxide (ZnO) were grown by the laser assisted flow deposition (LAFD) method. This new process has proved to be very efficient, allowing high yield ZnO deposits at high-rate applicable to large-scale substrates. Laser local heating promotes fast ZnO decomposition and recombination under a self-catalytic vapour–liquid-solid mechanism for the nucleation and growth. Three types of ZnO morphologies were obtained according to the temperature/oxygen availability inside the growth chamber. The morphology can also be controlled adding rare-earth elements to the initial composition. Particularly, tetrapod morphology was obtained by europium oxide addition to the precursors. The structural and microstructural characterizations confirm the good crystallinity of the wurtzite structure. The photoluminescence spectroscopy revealed high optical quality of the as-grown ZnO. Specifically, the free exciton recombination and a strong near band edge recombination due to donor bound exciton transitions can be clearly recognized, although deep level emission in the green spectral region is present.